The Effect Of Profitability, Value, Size and Managerial Discretion On Disclourse Of Stock Return - Santi Yustini; Yusar Sagara; Anis Saputri (Department of Accounting-Faculty of Economic and Business (FEB), 2018)
The objective of this study is to examine the effect of profitability that proxied by return on net operating assets and total asset turnover. Valuation is proxied by the price to book value. Size is proxied by total assets and Managerial Discretion is proxied by CEO Tenure. The analytical method used in this study is regression of bunches. The samples of this study are listed companies in property, real estate, and building construction that actively trading between 2013 until 2015 in Indonesia Stock Exchange.The results of this study indicate that the variable return on net operating assets, price to book value, size has a positive influence on the disclosure of stock return, while the total asset turnover and CEO tenure has no effect on the disclosure of stock return.